Tbx1 haploinsufficiency leads to local skull deformity, paraflocculus and flocculus dysplasia, and motor-learning deficit in 22q11.2 deletion syndrome - Tae-Yeon Eom; J. Eric Schmitt; Yiran Li; Christopher M. Davenport; Jeffrey Steinberg; Audrey Bonnan; Shahinur Alam; Young Sang Ryu; Leena Paul; Baranda S. Hansen; Khaled Khairy; Stephane Pelletier; et al. (Nature Communications)
Abstract Neurodevelopmental disorders are thought to arise from intrinsic brain abnormalities. Alternatively, they may arise from disrupted crosstalk among tissues. Here we show the local reduction of two vestibulo-cerebellar lobules, the paraflocculus and flocculus, in mouse models and humans with 22q11.2 deletion syndrome (22q11DS). In mice, this paraflocculus/flocculus dysplasia is associated with haploinsufficiency of the Tbx1 gene. Tbx1 haploinsufficiency also leads to impaired cerebellar synaptic plasticity and motor learning. However, neural cell compositions and neurogenesis are not altered in the dysplastic paraflocculus/flocculus. Interestingly, 22q11DS and Tbx1 +/– mice have malformations of the subarcuate fossa, a part of the petrous temporal bone, which encapsulates the paraflocculus/flocculus. Single-nuclei RNA sequencing reveals that Tbx1 haploinsufficiency leads to precocious differentiation of chondrocytes to osteoblasts in the petrous temporal bone autonomous to paraflocculus/flocculus cell populations. These findings suggest a previously unrecognized pathogenic structure/function relation in 22q11DS in which local skeletal deformity and cerebellar dysplasia result in behavioral deficiencies.